1980
DOI: 10.1246/bcsj.53.2055
|View full text |Cite
|
Sign up to set email alerts
|

The Substituent Effect. 15. The LSFE Treatment of Substituent Effects on Basicities of Pyridines

Abstract: The relative dissociation constants of meta and para substituted pyridinium ions in H2O at 25 °C were collected from a number of sources. To understand the actual substituent effects with a combination of inductive (I) and pi-electronic (Pi) effect components, the LSFE equation has been employed statistically for each of the meta and para series. ΔpK_a=ρ_iσ_i+ρ_π^+σ_π^++ρ_π^-σ_π^- The results illustrate (1) the I effect from the meta position is 1.2 times more effective than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…In para derivatives of benzene the inductive and resonance effects can be expressed as the sum of two components [10,11]. Therefore, the logarithms of the observed rate constants (k obs ) of p-substituted benzonitriles were correlated by using different inductive (localized) and resonance (delocalized) substituent constants.…”
Section: Resultsmentioning
confidence: 99%
“…In para derivatives of benzene the inductive and resonance effects can be expressed as the sum of two components [10,11]. Therefore, the logarithms of the observed rate constants (k obs ) of p-substituted benzonitriles were correlated by using different inductive (localized) and resonance (delocalized) substituent constants.…”
Section: Resultsmentioning
confidence: 99%
“…Later, analysis by the dual substituent parameter treatment 32 assigned ' R constants to the pyridinium ion system, and from a remark by Ellam and Johnson 33 a long controversy ensued. 13,29,[34][35][36][37][38] Basically, Johnson and co-workers 33,36,38 consider the pyridine reactivity to be closer to the benzoic acid reactivity rather than to the sigma-plus reactivities. Their contention was then supported only by Sawada et al 13 More recently, Reynolds et al 39 suggested that ' R BA and ' R scales could be replaced by a new ' R scale such that ' R BA values would be generated by linear interpolation between ' R and the new ' R values.…”
Section: Sigma Scale For Pyridine Reactivitymentioning
confidence: 99%
“…13,29,[34][35][36][37][38] Basically, Johnson and co-workers 33,36,38 consider the pyridine reactivity to be closer to the benzoic acid reactivity rather than to the sigma-plus reactivities. Their contention was then supported only by Sawada et al 13 More recently, Reynolds et al 39 suggested that ' R BA and ' R scales could be replaced by a new ' R scale such that ' R BA values would be generated by linear interpolation between ' R and the new ' R values. This suggests that the controversy could be settled by resorting to the YukawaTsuno analysis, insomuch that different r values associated with a single scale for resonance contributions would embrace the reactivities of benzoic acid, pyridinium ion, benzyl cation and a,a-dimethylbenzyl (or tertcumyl) cation derivatives.…”
Section: Sigma Scale For Pyridine Reactivitymentioning
confidence: 99%
See 2 more Smart Citations